Pengaruh Model Pembelajaran Berbasis Proyek Terhadap Keterampilan Berpikir Kreatif Dan Life Skill Siswa Pada Materi Jamur Di Smk Ponpes Abu Manshur Cirebon - Yuliana, Yuliana; Redjeki, Sri; Nur, Sofyan Hasanuddin (Edubiologica, 2020)
The problem of this research is how the influence of project-based learning models on students' creative thinking skills and life skills in the subject of fungi. The purpose of this study is to determine the effect of the application of project-based learning models on students' creative thinking skills and life skills in the subject of fungi. The research method used a quasi-experimental design with a pretest-posttest control group. The population in this study was all students of class X at SMK Ponpes Abu Manshur Cirebon in the academic year 2019/2020, with a purposive sampling technique used to select 50 students. Data collection techniques included tests, observation, and questionnaires. The results of this study are: (1) Students' creative thinking skills in the subject of fungi increased through the application of the project-based learning model, as evidenced by a significant difference in creative thinking skills between the experimental class and the control class with a probability value (p) of 0.001 < 0.05. (2) There was no significant difference in students' life skills through the application of the project-based learning model in the subject of fungi with a p-value of 0.083 > 0.05.